The importance of socio-demographic determinants and selected personality traits in shaping Poles' attitudes toward COVID-19 vaccination - Paduch, Jarosław; Syrowatko, Agnieszka; Żołnierczuk, Michał (Journal of Education, Health and Sport, 2021)
Objective: The aim of this study is to determine the level of particular personality traits and attitudes of Poles towards immunization, including against COVID-19, and to analyze potential predictors of these attitudes. Materials and methods: The online survey, conducted in September and October 2021, included 1466 individuals (50.6% female) aged 18 to 80 years (M = 42.81; SD = 12.46). The anonymous and voluntary online survey included original questions on attitudes toward immunization, including COVID-19 vaccination, rated on a 1-7 scale, past occurrence of NOP, and the Polish adaptation of the Ten Item Personality Inventory (TIPI)-TIPI-PL test. Results: It was shown that significant predictors of the level of acceptance of immunization were female gender, size of residence, education and past occurrence of NOP. In case of personality traits it was agreeableness, emotional stability and openness to experience. Sources of knowledge about vaccination were also significantly related: friends' opinions, Internet and experts' opinions. A higher level of agreeableness and openness to experience was correlated with a higher level of acceptance of vaccinations, whereas a higher level of emotional stability was correlated with a lower level of acceptance of vaccinations. Female gender, higher education and size of town of residence predisposed to acceptance of immunizations, whereas occurrence of vaccine adverse effect predisposed to low level of acceptance.